Influence of drawing methods on functional characteristics of precision aluminium tubes - Воденников, Сергей Анатольевич; Скачков, Виктор Алексеевич; Иванов, Виктор Ильич; Воденникова, Оксана Сергеевна (Technology audit and production reserves, 2014)
High gage interference, rigidity, strength and corrosion-resistance requirements are placed upon aluminum tubes, working in hard deformation conditions and corrosive media. Technological methods for ensuring specified requirements are quite complex and are based on a statistical description of the characteristics, implemented after each technological conversion of tube production. The possibility of using aluminum tubes in conditions of corrosive media implies their surface treatment with obtaining dense corrosion-resistant coatings. To assess gage interference, statistical methods, which together with experimental data have allowed to determine the ways of thickness stabilization and axis line curvature, are proposed. Fixed plug and moving-mandrel drawing reduces gage interference to an acceptable level. Conditions of reverse deformation for eliminating the axis line curvature to a given accuracy are defined. Predicting elastic and strength properties of the aluminum tubes in conditions of the structural anisotropy formation is possible using the methods, applied for complex loading and complex stress state of systems. Quantitative characteristic of crystallographic structures is based on the analytical estimation of crystallographic axes of crystals with respect to the laboratory axes, associated with the textured tube anisotropy. Technology of electrochemical oxidation and ematal coating of aluminum tube surfaces is developed. Influence of protective-hardening coating on the deflection value of tubes at three-point bending on the base of 560 mm with a force of 8.8 N is experimentally found.